Advances in Evolutionary and Deterministic Methods for Design, Optimization and Control in Engineering and Sciences - Minisci, Edmondo; Vasile, Massimiliano; Periaux, Jacques; Gauger, Nicolas R.; Giannakoglou, Kyriakos C.; Quagliarella, Domenico; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume presents up-to-date material on the state of the art in evolutionary and deterministic methods for design, optimization and control with applications to industrial and societal problems from Europe, Asia, and America. EUROGEN 2015 was the 11th of a series of International Conferences devoted to bringing together specialists from universities, research institutions and industries developing or applying evolutionary and deterministic methods in design optimization, with emphasis on solving industrial and societal problems. The conference was organised around a number of parallel symposia, regular sessions, and keynote lectures focused on surrogate-based optimization in aerodynamic design, adjoint methods for steady & unsteady optimization, multi-disciplinary design optimization, holistic optimization in marine design, game strategies combined with evolutionary computation, optimization under uncertainty, topology optimization, optimal planning, shape optimization, and production scheduling.
1. Keynote: Risk, Optimization and Meanfield Type Control, by Olivier Pironneau and Mathieu Laurière -- 2. Surrogate-Based Optimization in Aerodynamic Design -- A Review of Surrogate Modeling Techniques for Aerodynamic Analysis and Optimization: Current Limitations and Future Challenges in Industry, by Raul Yondo, Kamil Bobrowski, Esther Andrés and Eusebio Valero -- Constrained Single-Point Aerodynamic Shape Optimization of the DPW-W1 wing through Evolutionary Programming and Support Vector Machines, by E. Andrés-Pérez, D. González-Juárez, M. J. Martin-Burgos, L. Carro-Calvo -- Enabling of Large Scale Aerodynamic Shape Optimization through POD-based Reduced-Order Modeling and Free Form Deformation, by A. Scardigli, R. Arpa, A. Chiarini and H. Telib -- Application of Surrogate-based Optimization Techniques to Aerodynamic Design Cases, by Emiliano Iuliano and Domenico Quagliarella -- Efficient Global Optimization method for multipoint airfoil design, by Davide Cinquegrana and EmilianoIuliano -- 3. Adjoint Methods for Steady and Unsteady Optimization -- Checkpointing with time gaps for unsteady adjoint CFD, by Jan Christian Hueckelheim and Jens-Dominik Mueller -- Shape Optimization ofWind Turbine Blades using the Continuous Adjoint Method and Volumetric NURBS on a GPU Cluster, by Konstantinos T. Tsiakas, Xenofon S. Trompoukis, Varvara G. Asouti and Kyriakos C. Giannakoglou -- Aerodynamic Shape Optimization Using the Adjoint-based Truncated Newton Method, by Evangelos M. Papoutsis-Kiachagias, Mehdi Ghavami Nejad, and Kyriakos C. Giannakoglou -- Application of the adjoint method for the reconstruction of the boundary condition in unsteady shallow water flow simulation, by Asier Lacasta, Daniel Caviedes-Voullième and Pilar García-Navarro -- Aerodynamic Optimization of Car Shapes using the Continuous Adjoint Method and an RBF Morpher, by E.M. Papoutsis-Kiachagias, S. Porziani, C. Groth, M.E. Biancolini, E. Costa and K.C. Giannakoglou -- 4. Holistic Optimization in Marine Design -- Upfront CAD - Parametric modeling techniques for shape optimization, by S. Harries, C. Abt and M. Brenner -- Simulation-based Design Optimization by Sequential Multi-criterion Adaptive Sampling and Dynamic Radial Basis Functions, by Matteo Diez, Silvia Volpi, Andrea Serani, Frederick Stern and Emilio F. Campana -- Application of Holistic Ship Optimization in Bulkcarrier Design and Operation, by Lampros Nikolopoulos, Evangelos Boulougouris -- 5. Game Strategies Combined with Evolutionary Computation -- Designing Networks in Cooperation with ACO, by E. D'Amato, E. Daniele and L. Mallozzi -- Augmented Lagrangian approach for constrained potential Nash games, by Lina Mallozzi and Domenico Quagliarella -- A Diversity Dynamic Territory Nash Strategy in Evolutionary Algorithms: Enhancing Performances in Reconstruction Problems in Structural Engineering, by David Greiner, Jacques Périaux, J.M. Emperador, B. Galván, G. Winter -- Interactive Inverse Modeling Based Multiobjective EvolutionaryAlgorithm, by Karthik Sindhya and Jussi Hakanen -- Multi-Disciplinary Design Optimization of Air-breathing Hypersonic Vehicle Using Pareto Games and Evolutionary Algorithms, by Peng Wu, Zhili Tang, Jacques Periaux -- 6. Optimisation under Uncertainty -- Innovative methodologies for Robust Design Optimization with large number of uncertainties using modeFRONTIER, by Alberto Clarich, Rosario Russo -- A Novel Method for Inverse Uncertainty Propagation, by Xin Chen, ArturoMolina-Crist ´obal,Marin D. Guenov, Varun C. Datta, Atif Riaz -- Uncertainty Sources in the Baseline Configuration for Robust Design of a Supersonic Natural Laminar Flow Wing-Body, by Domenico Quagliarella and Emiliano Iuliano -- Robust Airfoil Design in the Context of Multi-Objective Optimization, by Lisa Kusch and Nicolas R. Gauger -- An alternative formulation for design under uncertainty, by F. Fusi and P. M. Congedo and G. Geraci and G. Iaccarino -- Polynomial Representation of Model Uncertainty in Dynamical Systems,by Massimiliano Vasile -- 7. Algorithms and Industrial Applications -- Improved archiving and search strategies for Multi Agent Collaborative Search, by Lorenzo A. Ricciardi, Massimiliano Vasile -- Comparison of Multi-objective Approaches to the Real-World Production Scheduling, by Gregor Papa and Peter Korošec -- Elucidation of Influence of Fuels on Hybrid Rocket Using Visualization of Design-Space Structure, by Kazuhisa Chiba, Shin'ya Watanabe, Masahiro Kanazaki, Koki Kitagawa, and Toru Shimada -- Creating Optimised Employee Travel Plans, by Neil Urquhart and Emma Hart -- A New Rich Vehicle Routing Problem Model and Benchmark Resource, by Kevin Sim, Emma Hart, Neil Urquhart, and Tim Pigden -- Genetic Algorithm Applied to Design Knowledge Discovery of Launch Vehicle Using Clustered Hybrid Rocket Engine, by Masahiro Kanazaki, Kazuhisa Chiba, Shoma Ito, Masashi Nakamiya, Koki Kitagawa and Toru Shimada -- Topology Optimization of Flow Channels with Heat Transfer Using a Genetic Algorithm Assisted by the Kriging Model, by Mitsuo Yoshimura, Takashi Misaka, Koji Shimoyama, Shigeru Obayashi -- Topology Optimization using GPGPU, by Stefan Gavranovic, Dirk Hartmann, Utz Wever. .
Keywords: Engineering design; Computational intelligence; Mathematics -- Data processing; Engineering Design; Computational Intelligence; Computational Mathematics and Numerical Analysis